COVID-19 incidence and the timing of quarantine measures and travel restrictions: A cross-country analysis - Marjorie C. Pajaron (University of the Philippines, School of Economics (UPSE), 2020)
Recent data on COVID-19 would suggest that no country is inured to the adverse effects of this disease. Although experts somehow agree on the virulence of the COVID-19 virus (SARS-CoV-2), it is puzzling why some countries have experienced the full brunt of the virus while others appear to have been totally spared. This paper examines one possible reason for the seemingly capricious nature of this virus. We compare the timing of the government response (travel restrictions and social distancing measures) of the ten ASEAN member countries and the incidence of COVID-19. Our preliminary results suggest that countries that responded relatively late (Indonesia, Philippines, Malaysia, and Thailand), when the local human-to-human transmission was already intense, have experienced a relatively high incidence of COVID-19 with the exception of Singapore and Cambodia. Further and more rigorous (regression) analysis is planned, conditional on data availability.
Keywords: H12; I15; I18; 330; COVID-19; Cross-country analysis; ASEAN